2018
DOI: 10.5194/cp-14-1499-2018
|View full text |Cite
|
Sign up to set email alerts
|

Extratropical cyclone statistics during the last millennium and the 21st century

Abstract: Abstract. Extratropical cyclones in winter and their characteristics are investigated in depth for the Atlantic European region, as they are responsible for a significant part of the rainfall and extreme wind and/or precipitation-induced hazards. The analysis is based on a seamless transient simulation with a state-of-the-art fully coupled Earth system model from 850 to 2100 CE. The Representative Concentration Pathway 8.5 (RCP8.5) scenario is used in the 21st century. During the Common Era, cyclone characteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 83 publications
7
31
0
Order By: Relevance
“…On the one hand, this suggests that recurrences of storminess become less statistically predictable outside the LIA. This may demonstrate that dynamic atmospheric processes are present in generating cyclone-related precipitation extremes throughout the LIA (Raible et al 2018), departing from the Clausius-Clapeyron thermodynamic expectations of an increase in precipitation intensity associated with atmospheric warming (Pall et al 2007, Trenberth 2011, Trenberth et al 2014, Kirby 2016, Prein and Pendergrass 2019. Our study thus shows the same tendency as revealed by Ljungqvist et al (2019) for a negative low-frequency temperature-hydroclimatic coupling (i.e., warm and dry) in southern Europe.…”
Section: Resultsmentioning
confidence: 46%
“…On the one hand, this suggests that recurrences of storminess become less statistically predictable outside the LIA. This may demonstrate that dynamic atmospheric processes are present in generating cyclone-related precipitation extremes throughout the LIA (Raible et al 2018), departing from the Clausius-Clapeyron thermodynamic expectations of an increase in precipitation intensity associated with atmospheric warming (Pall et al 2007, Trenberth 2011, Trenberth et al 2014, Kirby 2016, Prein and Pendergrass 2019. Our study thus shows the same tendency as revealed by Ljungqvist et al (2019) for a negative low-frequency temperature-hydroclimatic coupling (i.e., warm and dry) in southern Europe.…”
Section: Resultsmentioning
confidence: 46%
“…In this section, we analyse in how far these cyclone characteristics can help to explain the climate conditions in western and central Europe at the LGM and the frequent occurrence of dust storms in that area. According to the available proxy records, western and central Europe were colder and largely drier under LGM conditions (Bartlein et al, 2011;Annan and Hargreaves, 2013;Cleator et al, 2019) and were to a large extent covered by open shrublands and grasslands (Ray and Adams, 2001). The colder and generally drier conditions are reproduced by the Figure 6.…”
Section: Discussion With Available Proxy-based Climate Reconstructionsmentioning
confidence: 90%
“…The availability of studies addressing the characteristics of cyclone activity outside of the period extending from the mid-19th century to the end of the 21st century decreases sharply. Raible et al (2018) analysed variations of cyclone statistics in a very long simulation with a fully coupled Earth system model from 850 to 2100 CE. While they identified variations on multiple timescales, they found no evidence for an external forcing imprint before 1850.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations